Cell aging related genes can be used to characterize clinical prognoses and further stratify diffuse gliomas - Yang Yang (Nature Portfolio, 2021)
Abstract Increasing evidence has indicated that senescent cells are associated with the glioma development. Thus, we aimed to explore the relationship between the cellular senescence gene profile and the clinical prognosis of diffuse glioma. In total, 699 gliomas from The Cancer Genome Atlas (TCGA) dataset were used as the training cohort and 693 gliomas from the Chinese Glioma Genome Atlas (CGGA) dataset were used as the validation cohort. Bioinformatics statistical methods are used to develop the risk signature and to study the prognostic value of the risk signature. We identified a 14-gene risk signature and its risk score was an independent prognostic factor (P < 0.001) in the validation dataset. The risk signature had better prognostic value than traditional factors for the 3- and 5-year survival rate. Importantly, the risk signature could further stratify gliomas in specific subgroups of World Health Organization (WHO) classification by the survival rate. Furthermore, the mRNA levels of genes involved in the cell cycle, cell division and other processes were significantly correlated with the risk score. Our study highlighted a 14-gene risk signature for further stratifying the outcomes of patients with gliomas with definite WHO subgroups. These results indicate the potential clinical implications of cell aging-related genes in gliomas.